35. Synchronous Conferencing by a Community Advocacy Group - Fahrni, Patricia (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2004)
The previous report in this series discussed how collaborative tools can be used in the development of formal and non-formal online communities. The current report describes the specific development of an online community advocacy group.